Parenting: fears and medical reinsurance - Mutchinick, Mercedes; Terceiro, Diego (Revista del Hospital Italiano de Buenos Aires, 2018)
It is very frequent in Family Physicians practices, to receive consultations where the context of the patient and his family are directly related to their health problems. We have a fundamental place to evaluate these aspects and guide our patients in the resolution of these problems. To carry out this task is necessary to have time, be interested and receive some training. The family doctors of the Hospital Italiano de Buenos Aires developed a specific device called FOCO (Family, Orientation and COntext) in order to provide our patients with advice, containment, guidance and, eventually, treatment of psychosocial, contextual or family aspects. In addition, we believe that this device also serves to be able to translate in clinical history aspects usually not transcribed in it, related to the clinical encounter. We present the case of a family with a fearful mother who thinks that “more is better” in the care of their children and their approach through the FOCO device